Mechanism of the diuretic activity of Descurainia sophia seed (Bangladesh Journal of Pharmacology, 2018)
The diuretic activity of the decoction and the chemical fractions of Descurainia sophia was studied with underlying mechanisms in rats. Rat metabolic cage method was used to study the diuretic activity of the decoction and the chemical fractions of D. sophia. Western blot, ELISA, ion selective electrode method and cryoscopy method were used to study the underlying mechanism. The urinary output increased significantly in rats administrated decoction. Washing elution fractions had the potent diuretic activity. Washing elution fractions could decrease the urine osmolality, increased the concentration of K+, and decreased the concentration of Na+ and ALD, also decreased the expression of aquaporin 1 (AQP1) in kidney. Moreover, compared with washing elution fractions, decoction decreased the levels of AVP, V2R, and AQP2. It is concluded that decoction had significant diuretic activity and washing elution fractions had the potent diuretic activity. The mechanisms of diuretic activity were different between decoction and washing elution fractions.Video Clip of Methodology: 10 min 51 sec:   Click to watch